THE EFFECT OF SELF SERVICE TECHNOLOGY (SST) AND APPLICATION FEATURES ON SATISFACTION WITH THE USE OF MOBILE BANKING BY BSI IN UIN NORTH SUMATRA STUDENTS - Audri Fadillah Saputri; Nurbaiti; Aqwa Naser Daulay (International Journal of Cultural and Social Science, 2025)
This study investigates the effects of Self-Service Technology (SST) and Application Features on user satisfaction in using BSI Mobile banking among students at the State Islamic University of North Sumatra. Employing a quantitative approach with associative analysis, the study utilized purposive sampling to select 100 respondents from a population of 23,671 students. Data were collected via an online questionnaire using Google Forms and analyzed with SPSS Version 25. The results indicate that both SST and Application Features partially have a positive and significant effect on user satisfaction. Simultaneously, SST and Application Features together significantly influence user satisfaction. The coefficient of determination (Adjusted R²) is 0.548, indicating that 54% of the variance in user satisfaction can be explained by SST and Application Features, while 46% is influenced by other factors not examined in this study. These findings provide practical insights for BSI to enhance mobile banking satisfaction by improving both technological aspects and application functionalities.